Current and emerging treatments for severe asthma - Al Efraij, Khalid (J Thorac Dis, 2015)
Severe asthma, which is poorly controlled despite the elimination of modifiable factors and the correct use of standard therapy, accounts only for 5% of people with asthma but it contributes to approximately 50% of the economic costs of asthma. Because of this unmet need, novel therapies have been developed for optimal treatment of these patients. The use of tiotropium, omalizumab, mepolizumab and thermoplasty in well-selected patients provides better control and most importantly a reduction in asthma exacerbations.